Comparative emergency management : examining global and regional responses to disasters - Miller, DeMond Shondell, 1973-; Rivera, Jason David, 1983- (CRC Press, 2011)
A host of natural and man-made disasters have plagued the world in the twenty-first century, many with significant global impact. The Deepwater Horizon Oil Spill, the Indian Ocean tsunami, and Hurricane Katrina all affected broad regions with devastating results. The need for better emergency management policies, procedures, and cooperation among nations is evident. Bringing together contributions from a cadre of international experts, Comparative Emergency Management: Examining Global and Regional Responses to Disasters demonstrates ways to recognize and reduce regional infrastructure vulnerability by building secure networks of collaboration within different geographical areas of the world. Explores issues on all continents With discrete sections on the Americas, Africa and the Middle East, Europe, Asia, and the Pacific Rim, the book presents the work of researchers and practitioners who examine ways different societies have responded to environmental threats using innovative methods to cope with their vulnerabilities to disaster. Topics discussed include: A game approach that has been used as an effective tool in the communication of disaster risk information in the Caribbean Efforts to rebuild tourism in New Orleans despite the challenges presented by media coverage of Hurricane Katrina Faith-based organization (FBO) humanitarian assistance in the Muslim world Nongovernmental and community-based responses to the Asian tsunami and the Sumatran earthquake. The book presents a multifaceted study that aims to foster dialogue among policymakers to reduce social vulnerability and build local and regional capacities to withstand environmental assaults. Encouraging creative thinking, it offers ideas and solutions that have been successful in a range of environments worldwide. The authoritative scholarship presented combines interdisciplinary studies that will be valuable to a broad range of fields and professionals.